Lactational exposure to venlafaxine provokes late repercussions on reproductive parameters in male rat offspring - Moreira, Suyane da Silva [UNESP]; Manoel, Beatriz de Matos; Inacio, Joao Pedro Gaspar [UNESP]; Souza, Carolina Gabrielli de [UNESP]; Reis, Ana Carolina Casali [UNESP]; Jorge, Barbara Campos [UNESP]; Aquino, Ariana Musa de [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Cardoso, Claudia Lima Andrea; Arena, Arielle Cristina [UNESP] (Wiley-Blackwell, 2022)
Exposure to selective serotonin reuptake inhibitors can affect hormone-dependent processes, such as the brain sexual differentiation. Because the use of these antidepressants cause concern during lactation, we evaluated the possible effects of venlafaxine on lactational exposure and its late repercussions on reproductive parameters in male rats. Lactating rats were exposed to venlafaxine (3.85, 7.7, or 15.4 mg/kg/body weight; gavage), from lactational day 1 to 20. Venlafaxine and O-desmethylvenlafaxine residues were found in all milk samples of dams treated, demonstrating the lactational transfer of this antidepressant to the offspring. Although the maternal behavior was normal, the dams presented an increase in urea and uric acid levels in the groups treated with 7.7 and 15.4, respectively, as well as a spleen weight increased in the 3.85 and 15.4 groups. The male offspring showed a decrease in play behavior parameters in the intermediate dose group. Sperm analysis indicated a reduction in sperm motility in all treated groups. The androgen receptor expression in the hypothalamus was decreased in the highest dose group, although the sexual behavior had not been affected. In conclusion, venlafaxine was transferred through breast milk and promoted changes in play behavior, sperm quality, and hypothalamic androgen receptor (AR) content, which may indicate an incomplete masculinization of the brain of male offspring.
Keywords: Brain sexual differentiation; Maternal milk; Postpartum depression; Serotonin; Sexual behavior